Pengembangan Instrumen Berpikir Kritis Matematis Peserta Didik Sekolah Dasar - Putri, Hafiziani Eka; Fitri, Rizka Malfiana; Rahayu, Teten Ginanjar; Nurussama, Alfiana; Hikmatunisa, Nenden Permas; Santos, Mariano Dos (Institut Agama Islam Negeri Kendari, 2026)
Mathematical Critical Thinking (MCT) is a key 21st-century competency, yet elementary students’ MCT skills remain underdeveloped, partly due to the lack of age-appropriate assessment instruments. Existing instruments primarily target secondary and higher education and inadequately represent critical thinking indicators in elementary mathematics. This study aimed to develop and evaluate the validity and reliability of an MCT instrument on integer addition and subtraction for elementary students. Using a Research and Development (R&D) approach with the ADDIE model, the instrument was tested on 17 third-grade students at an elementary school in Purwakarta through purposive sampling. Nine essay items were designed based on six indicators: interpretation, analysis, inference, evaluation, explanation, and self-regulation. The results showed a reliability coefficient of 0.88, with item difficulty ranging from easy to moderate and good discrimination indices. Five items met validity criteria and were deemed suitable for assessing elementary students’ mathematical critical thinking skills.